Diversity of Shrimp Species Based on Fishermen's Catches in the Coastal Area of Pematang Cengal Village, Langkat Regency, North Sumatra: Keanekaragaman Jenis Udang Berdasarkan Hasil Tangkapan Nelayan Kawasan Pesisir Desa Pematang Cengal, Langkat, Sumatera Utara - Jayanthi, Sri; Astuti, Sri Pujianti; Nur, Siti Fadhilah; Nabila, Shifa; Pepayosa, Enca (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2025)
The This study aims to determine the diversity, morphology, and morphometric studies of shrimp caught by fishermen in the coastal area of Pematang Cengal Village, Tanjung Pura, North Sumatra. The study was conducted on June 9-12, 2025, using a quantitative descriptive method. Sampling was carried out through interviews with fishermen and direct observation of the catch. The results of the study found 10 species of shrimp consisting of 3 families (Penaeidae, Palaemonidae, and Squillidae) from 2 orders (Decapoda and Stomatopoda). The shrimp species found were Penaeus merguiensis, Penaeus monodon, Palaemonid shrimps, Harpiosquilla raphidea, Parapenaeopsis sculptilis, Penaeus indicus, Metapenaeus affinis, Litopanaeus vannamei, Macrobrachium rosenbergii, and Metapeneus brevicornis. Morphometric measurements showed different variations between shrimp species. Based on total length, the size of shrimp caught in the Pematang Cengal Village Coastal Area is relatively stable and falls into the medium-sized category. This research provides important information regarding shrimp species diversity in the Pematang Cengal Village coastal area and can serve as a starting point for shrimp resource conservation in the area.